2011
DOI: 10.1186/ar3458
|View full text |Cite
|
Sign up to set email alerts
|

Ossification process involving the human thoracic ligamentum flavum: role of transcription factors

Abstract: IntroductionOssification of the ligamentum flavum (OLF) of the spine is associated with serious neurologic compromise, but the pathomechanism of this process remains unclear. The objective of this study was to investigate the pathomechanism of the ossification process, including the roles of various transcriptional factors in the ossification of human thoracic ligamentum flavum.MethodsSections of the thoracic ligamentum flavum were obtained from 31 patients with OLF who underwent posterior thoracic decompressi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
38
0
1

Year Published

2013
2013
2018
2018

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 37 publications
(42 citation statements)
references
References 36 publications
3
38
0
1
Order By: Relevance
“…25,34,37 Although it has been 90 years since the first description of OLF, very little is known about the pathophysiology of OLF. Currently, several studies have described the possible roles of mechanical/traumatic, 14 [50][51][52][53] in the development and progression of OLF.…”
Section: Discussionmentioning
confidence: 99%
“…25,34,37 Although it has been 90 years since the first description of OLF, very little is known about the pathophysiology of OLF. Currently, several studies have described the possible roles of mechanical/traumatic, 14 [50][51][52][53] in the development and progression of OLF.…”
Section: Discussionmentioning
confidence: 99%
“…In our previous study using reverse-transcriptase polymersae chain reaction, we have demonstrated that cultured cells derived from ossifi ed spinal ligament express high levels of Sox9 and Runx2. 15 Sox9 is known to promote chondrocyte differentiation, and Runx2 promotes the differentiation of premature chondrocytes to hypertrophic chondrocytes. 16 Considering these results, we hypothesize that overexpression of Sox9 and Runx2 is due to differences in genetic background.…”
Section: Fibroblasts (Fiber Area)mentioning
confidence: 99%
“…25 In this study, these transcription-activating histone modifications and transcription factors localized to the same area. Therefore, we hypothesize that histone modifications (H3K18ac, H3K9ac, H3K4me3, and H3K36me3) create a favorable microenvironment for transcription factors (osterix and Runx2) to access osteogenic genes during ossification.…”
Section: 27mentioning
confidence: 99%